A Case of Brucellosis Presenting with Multiple Hypodense Splenic Lesions and Bilateral Pleural Effusions. (25th May 2011) - Eruz, Emine Dilek; Birengel, Serhat; Azap, Alpay; Bozkurt, Gulden Yilmaz
Abstract : Brucellosis is a zoonotic infectious disease, which mainly present with lymphoreticular system invovement. However any organ system can be attacked by the microorganism. In this paper we present a 52-year-old female patient who was admitted to the Infectious Diseases Department with complaints of fatigue, arthralgias, fever, and weight loss. In the medical examination and radiological analysis bilateral pleural effusions and hepatosplenomegaly were detected. Serum transaminase levels were two times higher than the upper limits of normal. Abdominal ultrasound revealed sludge in the gallbladder and multiple hypodense splenic lesions (the largest was 1 cm in diameter). Brucella melitensis was isolated from the blood culture of the patient. Rifampicin (600 mg/day) and doxycycline (200 mg/day) therapy was started. Follow-up chest radiography and ultrasonography revealed the absence of pleural effusion. Splenic lesions and hepatosplenomegaly were totally regressed. The patient has been followed for 3 months after 6 week antibiotic regimen without recurrence. Brucellosis was expected to be the cause of all pathological signs.